2022
DOI: 10.1111/lam.13707
|View full text |Cite
|
Sign up to set email alerts
|

Purpureocillium lilacinum an emergent pathogen: antifungal susceptibility of environmental and clinical strains

Abstract: Purpureocillium lilacinum is a filamentous and hyaline fungus cosmopolitan, saprophytic, largely used in the biological control of plant‐parasitic nematodes and insects, also considered an emerging and opportunistic human pathogen. The standard treatment for hyalohyphomycosis caused by P. lilacinum is not yet defined, since this fungus is resistant to different antifungals, in vitro and in vivo. The aim of this study was to evaluate and compare in vitro antifungal activity against environmental and clinical P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our case, oral administration of VRCZ effectively reduced the size of swollen lymph nodes and lowered the biomarker levels. The low MIC of this isolate to VRCZ was consistent with the data of several reports showing that P. lilacinum clinical isolates have low MICs to VRCZ and posaconazole [ 4 , 15 ]. Although the breakpoint has yet to be established [ 4 , 15 ], ECMM and ISHAM recommend VRCZ as a first-line therapy in Global Guideline for the Diagnosis and Management of Rare Mold Infections [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…In our case, oral administration of VRCZ effectively reduced the size of swollen lymph nodes and lowered the biomarker levels. The low MIC of this isolate to VRCZ was consistent with the data of several reports showing that P. lilacinum clinical isolates have low MICs to VRCZ and posaconazole [ 4 , 15 ]. Although the breakpoint has yet to be established [ 4 , 15 ], ECMM and ISHAM recommend VRCZ as a first-line therapy in Global Guideline for the Diagnosis and Management of Rare Mold Infections [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…There are only a few clinical cases of P. lilacinum , so no standard antifungal regimens exist[ 10 ]. Aguilar et al [ 11 ] showed early on that amphotericin B, miconazole, itraconazole, fluconazole, and flucytosine are less active against penicillium[ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one experimental murine study, the subcutaneous inoculation of P. lilacinum caused comparable damage to animal tissue, including dermatitis, panniculitis, and skin ulcerations with a diffuse inflammatory infiltrate in both immunosuppressed and immunocompetent mice. However, the lesions in immunosuppressed mice were more severe, including extensive areas of ulcers covered with crust, dermatitis, and suppurative panniculitis, with more fungal structures observed on histological slides [18]. Ulcerations are the result of angioinvasion, in both humans and mice.…”
Section: Cutaneous Infectionsmentioning
confidence: 99%
“…Histopathologically, many of these fungi tend to invade blood vessels and produce hemorrhagic necrosis and tissue infarction [6], clinically presented as ulcerative lesions (e.g., Purpureocillium lilacinum) or eschars (e.g., Fusarium spp.) [17,18]. Figure 1 summarizes the spectrum of cutaneous hyalohyphomycosis, and associates various forms of cutaneous infections with the most common causative agent according to the reported cases.…”
Section: Hyalohyphomycosismentioning
confidence: 99%
See 1 more Smart Citation